PENUNJANG KEPUTUSAN PENGADAAN INPUT DALAM RANTAI PASOK PENGOLAHAN COKELAT PADA BUMDES â€œMOTOTOMPIAANâ€ DESA POYUYANAN - Shinta M. Tengor; Mex L. Sondakh; Tommy F. Lolowang (Universitas Sam Ratulangi, 2015)
ABSTRACT Supply Chain Management is an activity that is interconnected and dependence on one another, ranging from ordering raw materials to finished product delivered to the consumer. The goal is the coordination of various activities in the production process and the parties involved. Uncertainties or constraints along the supply chain will make the service meeting the needs of consumers into decline and uninterrupted production process. Need the right decisions especially in the procurement of input because these activities are carried out initial production. Therefore, a decision maker needs a decision support that can help provide a consideration in the decision-making activities. The purpose of this study was to obtain a decision support regarding the procurement of inputs, especially in the selection of the best suppliers and the selection of products with the potential to be developed.The results showed that the selection of suppliers are processed using the Delphi method produces District of North Dumoga as a supplier who has the highest score of 5.4 followed by Kecamatan East Dumoga with a value of 5.2. While the determination of potential products are processed using MPE products Milk Chocolate / Chocolate Trunk as potential products to be developed, with a value of 397 303 882. Keywords :Supply Chain Management , Decision Support , Suppliers , Products.